School-family partnerships for children's success - Patrikakou, Evanthia N.; Weissberg, Roger P.; Redding, Sam (Series on social emotional learning, 2005)
"In this groundbreaking volume, the most influential leaders in the field provide essential information to better understand and improve the nature and quality of school-family partnerships for the benefit of all children. These experts examine the various aspects and effects of parental involvement not only on children's academic achievement, but also on their social and emotional development. Featuring a comprehensive multidimensional framework, the text addresses critical issues facing families and educators, developmental considerations, cultural perspectives, and policy issues. Each chapter includes recommendations to help educators, parents, and policymakers create and sustain successful partnerships to support children's development."--Book jacket.